Thioredoxin Modulates Protein Arginine Deiminase 4 (PAD4)-Catalyzed Citrullination - Nagar, Mitesh; Tilvawala, Ronak; Thompson, Paul R. (Frontiers in Immunology, 2019)
Protein citrullination plays a crucial role in the pathophysiology of numerous autoimmune disorders including Rheumatoid Arthritis (RA). Recently, there has been a growing interest in investigating the physiological regulators of the protein arginine deiminases (PADs), which catalyze this modification. Apart from calcium, it is well documented that a reducing environment activates the PADs. Although the concentration of thioredoxin (hTRX), an oxidoreductase that maintains the cellular reducing environment, is elevated in RA patients, its contribution towards RA progression or PAD activity has not been explored. Herein, we demonstrate that hTRX activates PAD4. Kinetic characterization of PAD4 using hTRX as the reducing agent yielded parameters that are comparable to those obtained with the non-physiological reducing agent DTT, suggesting the importance of hTRX in PAD regulation under physiological conditions. Furthermore, we show that various hTRX mutants, including redox inactive hTRX variants, are capable of activating PAD4. These data demonstrate that hTRX activates PAD4 via a mechanism that does not require oxidoreductase activity. Indeed, we observed non-covalent interactions between PAD4 and hTRX variants, and propose that these redox-independent interactions are sufficient for hTRX mediated PAD4 activation.